2006
DOI: 10.1097/01.mnm.0000202864.52046.b1
|View full text |Cite
|
Sign up to set email alerts
|

Normal values of [99mTc]pertechnetate uptake and excretion fraction by major salivary glands

Abstract: The assessment of the functional status of the salivary glands has been used in the scintigraphic evaluation of xerostomia. Several quantitative methods derived from standard dynamic scintigraphy have been suggested. However, the indices proposed are quite variable and unlikely to be useful in clinical practice. The objectives of this study were to obtain reference values of major salivary glands uptake and excretion fraction in healthy subjects and to obtain normal ratios of Tc-pertechnetate uptake by the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 19 publications
1
36
1
4
Order By: Relevance
“…On the basis of the departmental reference values, these participants would have been diagnosed as abnormal. Although these data overlap considerably with other ranges reported elsewhere, [7][8][9] they differ significantly. From the current findings, gender, age and ethnicity did not appear to significantly influence euthyroid uptake of technetium-99m pertechnetate.…”
Section: Discussioncontrasting
confidence: 51%
“…On the basis of the departmental reference values, these participants would have been diagnosed as abnormal. Although these data overlap considerably with other ranges reported elsewhere, [7][8][9] they differ significantly. From the current findings, gender, age and ethnicity did not appear to significantly influence euthyroid uptake of technetium-99m pertechnetate.…”
Section: Discussioncontrasting
confidence: 51%
“…[7][8][9] Therefore, there is a need to establish reference values for each location.There are no reported reference values for technetium-99m pertechnetate uptake for Namibia. The reference range routinely used in Namibia for thyroid uptake of technetium-99m pertechnetate is 0.75-4% of the administered activity after 20 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…It is well tolerated by patients because it is suitable for normal physiology (17)(18)(19)(20)(21)(22). A literature review of the quantitative evaluation of salivary gland functions created from dynamic studies showed that most functional parameters, for example percentage uptake, concentration, and excretion fractions, were generated from individual salivary gland timeactivity curves (6)(7)(8)(23)(24)(25) to acquire reference values of salivary gland uptake and excretion fraction in 50 healthy volunteers (7). In our study, evaluation of salivary gland function was performed by radionuclide imaging, and we found that there were significant decreases in the salivary gland functions of patients using isotretinoin at months 3 and 6 compared to pretreatment values.…”
Section: Discussionmentioning
confidence: 99%
“…injection. Quantitative functional data, for example uptake ratio, concentration, and excretion fraction, can be obtained via radionuclide imaging of the salivary glands (6)(7)(8). Evaluation of salivary gland function according to objective criteria, rather than subjective complaints, may provide an accurate assessment of patients taking isotretinoin and suffering from dry mouth.…”
Section: Introductionmentioning
confidence: 99%